The effect of cutting speed on the roughness level of low carbon steel cutting results using the trulaser 3030 machine - Amron, Husni; Roziqin, Ahmad (JMEL : Journal of Mechanical Engineering Learning, 2024)
This research aims to determine the effect of variations in cutting speed on the roughness value of low carbon steel cutting results using CNC Laser Cutting TruLaser3030. This research uses experimental methods and descriptive statistical data analysis techniques and diagrams to present data on the measurement results of research specimens using cutting speeds of 2520 mm/minute, 2205 mm/minute, and 1890 mm/minute. Roughness testing was carried out using Surface Roughness Mitutoyo SJ-210. The results of the research produced data showing that the higher the cutting speed, the roughness value increases and the lower the cutting speed, the roughness value will decrease. And if the cutting speed is too high then the material cannot be cut. The lowest roughness value, namely 8.46µm, was at a cutting speed variation of 1980 mm/minute. The highest roughness value, namely 23.63µm, occurs at a cutting speed variation of 2520 mm/minute.